Efektivitas Program Pelayanan Posyandu Terkait Penanggulangan dan Pencegahan Stunting - Kalani, Fidelia Helvin; Pajung, Christian Bertom; Toar, Jilly (Yayasan Syalom Cipta Sumikolah, 2025)
Stunting is still a serious public health problem in Indonesia, especially in rural areas. Lembang Sa'Tandung is an area with the highest number of stunting cases in the Ulusalu Health Center working area, Tana Toraja Regency. This study aims to determine the effectiveness of the posyandu service program in overcoming and preventing stunting in the area. The study used a qualitative approach with data collection techniques through in-depth interviews, observation, and documentation with four key informants: puskesmas officers, village midwives, posyandu cadres, and mothers of children under five. Data analysis was conducted using the Miles and Huberman interactive model. The results showed that the posyandu program has been implemented routinely and targets risk groups through monitoring child growth and development, providing additional food (PMT), and nutrition counseling. There has been an increase in nutritional awareness among mothers of children under five. However, the effectiveness of the program has not been optimal because there are still obstacles such as limited budget, lack of facilities and health workers, low community literacy, and lack of consistency of counseling activities and cross-sector coordination. Strengthening education, increasing the capacity of cadres, and cross-sector collaboration are needed to support the success of the program.